Dignity, Human Rights, and Democracy - Garzón Valdés, Ernesto; Justus Liebig University Giessen (My University, 2009)
In order to analyze what can plausibly be said about the relationship between dignity, human rights, and democracy, I will propose a basic assumption about human dignity (I) and then formulate five theses concerning the justification of democracy (II) which will allow me to conclude (III) that only when human rights are constitutionally established and effectively implemented democracy can be theoretically and practically justified as a political means to guarantee human dignity.
Keywords: ddc:100; ddc:330